2006
DOI: 10.1111/j.1444-2906.2006.01189.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of microbial diversity in the river trout Salmo trutta fario L. intestinal tract identified by partial 16S rRNA gene sequence analysis

Abstract: The microbial diversity of the intestinal tract content of the river trout from two Lithuanian rivers has been investigated by molecular methods: polymerase chain reaction amplification and sequencing of partial 16S rRNA genes. Predominant bacterial populations detected in the river trout intestinal tract from the Skroblus River were Rahnella (21%), from the Xeimena River, Aeromonas (41.7%) and Plesiomonas (22.9%). Buttiauxella agrestis, Budvicia aquatica, Erwinia persicinus, Yersinia mollaretii, Y. kristensen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 25 publications
3
30
0
1
Order By: Relevance
“…With regard to the taxonomic identification of the TM and LAB, our results (Table 1) point to the instability of the composition of the rainbow trout intestine microbiota along the fish life-cycle, which has been previously described for other salmonids [24]. With regard to this, at the larval stage, the predominant intestinal TM belonged to the family Aeromonadaceae, and mainly to the genus Aeromonas, which is in agreement with a previous study on river trout (Salmo trutta) [25]. On the other hand, in our study, the intestinal microbiota found from the growth stages F1 to A2 was dominated by Enterobacteriaceae (mainly the genera Citrobacter, Kluyvera and Enterobacter), similarly as previously described [26].…”
Section: Discussionsupporting
confidence: 91%
“…With regard to the taxonomic identification of the TM and LAB, our results (Table 1) point to the instability of the composition of the rainbow trout intestine microbiota along the fish life-cycle, which has been previously described for other salmonids [24]. With regard to this, at the larval stage, the predominant intestinal TM belonged to the family Aeromonadaceae, and mainly to the genus Aeromonas, which is in agreement with a previous study on river trout (Salmo trutta) [25]. On the other hand, in our study, the intestinal microbiota found from the growth stages F1 to A2 was dominated by Enterobacteriaceae (mainly the genera Citrobacter, Kluyvera and Enterobacter), similarly as previously described [26].…”
Section: Discussionsupporting
confidence: 91%
“…Genomic DNA was extracted from the isolates following the method reported by Skrodenyte-Arbaciauskiene et al (2006b). Universal bacterial primers w001 F8 (59-AGAGTTTGATCMTGGCTC-39) and w002 R1509 (59-GNTACCTTGTTACGACTT-39) (Godon et al, 1997) were used to amplify 16S rRNA gene sequences.…”
mentioning
confidence: 99%
“…The digestive endosystem contains micro-organisms which use for their nutrition the substances isolated by other microorganisms during metabolism [24][25][26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%